Trap-nesting bees (Hymenoptera, Apoidea) in areas of dry semideciduous forest and caatinga, Bahia, Brazil - Aguiar,Cândida M. L. (2005)
In this study were examined the species richness and seasonal abundance of cavity-nesting bees in areas of dry semi-deciduous forest and caatinga in the State of Bahia, Brazil. Sampling was done employing two types of trap-nests: bamboo canes and tubes made of black cardboard with dimensions of either 58 x 6 mm or 105 x 8 mm. The traps were inspected once a month. One hundred and forty-six nests of 11 bee species were collected in the forest, and 121 nests of seven species were collected in the caatinga. Five species of cleptoparasitic bees were also reared from these nests. The highest nesting frequencies occurred in the wet season in both areas. Nests parasitism was important only for Centris tarsata Smith, 1874, and was higher at the caatinga site than in the forest. The mortality of pre-emergent adults was high, especially in C. tarsata,Tetrapedia diversipes Klug, 1810 and Euglossa cordata (Linnaeus, 1758). Information on the number of cells per nest, the size, shape, and arrangement of brood cells in the nests, as well as the number of adults produced and the number of generations per year are also presented. Species richness, temporal patterns of nesting, and percentage of parasitism were compared with other habitats.